Work-related stressors of secondary school teachers: Basis for developing a stress management program - Mary Jean P. Dureza; Lea M. Madulid; Peter Marc D. Magsalin; Lyra B. Matulina; Sara M. Villanueva (Northern Negros State College of Science and Technology (NONESCOST), 2022)
This descriptive action research aimed to determine the work-related stressors of secondary school teachers' experience, particularly in the school. Based on the gathered data, it is evident that the majority of secondary school teachers have to adjust to the evolving way of teaching. The hybrid approach to teaching and learning (face-to-face and online) takes a toll on teachers' preparation. Utilizing several tools and platforms and incorporating various techniques to engage learners has caused teachers to spend significant time and resources in preparation. On top of it, the additional clerical and administrative tasks have caused the secondary school teachers to be exhausted and under pressure daily. Adapted survey questionnaires were administered to assess the respondents' stressors, particularly at school. There was a total of eighty-four (84) purposely selected secondary school teachers/faculty members. Furthermore, a five-point Likert scale was employed to determine the respondents' results, eventually leading to data interpretation using descriptive ratings. On the other hand, Cronbach Alpha was used to check the internal validity of the surveys with a result of .87 for the first part of the questionnaires (work-related stressors experienced) and .94 for the second part (extent effect of work-related stress) which are both acceptable. The results reveal that secondary school teachers' main causes of stress were multitasking at work with a mean of (M=3.97) followed by tedious tasks at work with a mean of (M=3.44). Negative stress has caused a tremendous burden on school teachers. According to respondents, the emotional aspect requires immediate attention to reduce stress. This aspect receives the highest response of 45% followed by the physiological aspect at 24%. Primary consideration is given to the conduct of action research to determine whether secondary school teachers are emotionally, mentally, and physically in excellent health. The findings led to the development of a stress management program (SMP) specifically designed for secondary school teachers.